Some mortality patterns of Greater Magellan Geese on the Falkland Islands - Harradine, John (Wildfowl, 1982)
Intestinal parasites were commonly present in sick or dead and apparently healthy wild Greater Magellan Geese Chlophaga picta leucoptera. The nematode gizzard worm Amidostomum anseris, various hymenolepid cestodes in the small intestine and the nematodes Heterakis dispar and Trichostrongylus tenuis in the caecae, occurred most frequently. Apart from the gizzard worms they had little obvious effect on the geese. Degeneration of the goose’s gizzard, however, can seriously affect its ability to feed and may, on occasion, be the primary cause of death. Congregation on short pastures, especially in winter when stress from food shortage can occur, facilitates the transmission of gizzard worm and probably contributes to the periodic die-offs. A 1:1 sex ratio was found at hatching (22 complete clutches) and around fledging (644 birds) but the ratio was 1:1.3 (2,656 birds) amongst sub-adult and adult Greater Magellan Geese. The reasons for the differential mortality of males are not clear but may include their greater susceptibility to food shortage and its enhancement of disease, and hunting mortality.